Temperature as the basic factor influencing phenological stages in Ziziphus jujuba Mill - Saket Mishra; Boris Krška (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2009)
The present study to find a suitable base temperature for different phenological stages in Ziziphus jujuba Mill”. The data from the automatic meteorological station AMET located inside the orchard were used for the analyses. Since 2006, the automatic station has provided data on the atmosphere condition on a regular quarter-hour basis. The analysis was conducted on the basis of two years observations (2006–2007). To find out the suitable base temperature for phenology in jujube, we used the sum of active hourly temperatures (hour stages). Evaluations were carried out for each year, 2006 and 2007. In accordance with published data, the base temperatures above 7, 9 and 11 °C were used as threshold values for the phenology of jujube. Statistical evaluations of the data showed differences between 2006 and 2007. On the basis of active hourly temperatures (7, 9 and 11 °C), statistically analyzed average 1 day differences during 2006 and 2007 were computed from the previous 10 days to find out the differences between suitable and recorded dates of the start of each phenological phase, in days. On the basis of these results, 11°C is the most suitable base temperature for jujube.